"Protein aggregates" contain RNA and DNA, entrapped by misfolded proteins but largely rescued by slowing translational elongation. Issue 5 (31st March 2021) - Shmookler Reis, Robert J.; Atluri, Ramani; Balasubramaniam, Meenakshisundaram; Johnson, Jay; Ganne, Akshatha; Ayyadevara, Srinivas
Abstract: All neurodegenerative diseases feature aggregates, which usually contain disease‐specific diagnostic proteins; non‐protein constituents, however, have rarely been explored. Aggregates from SY5Y‐APPSw neuroblastoma, a cell model of familial Alzheimer's disease, were crosslinked and sequences of linked peptides identified. We constructed a normalized "contactome" comprising 11 subnetworks, centered on 24 high‐connectivity hubs. Remarkably, all 24 are nucleic acid‐binding proteins. This led us to isolate and sequence RNA and DNA from Alzheimer's and control aggregates. RNA fragments were mapped to the human genome by RNA‐seq and DNA by ChIP‐seq. Nearly all aggregate RNA sequences mapped to specific genes, whereas DNA fragments were predominantly intergenic. These nucleic acid mappings are all significantly nonrandom, making an artifactual origin extremely unlikely. RNA (mostly cytoplasmic) exceeded DNA (chiefly nuclear) by twofold to fivefold. RNA fragments recovered from AD tissue were 1.5‐to 2.5‐fold more abundant than those recovered from control tissue, similar to the increase in protein. Aggregate abundances of specific RNA sequences were strikingly differential between cultured SY5Y‐APPSw glioblastoma cells expressing APOE3 vs. APOE4, consistent with APOE4 competition for E‐box/CLEAR motifs. We identified many G‐quadruplex and viral sequences within RNA and DNA of aggregates, suggesting that sequestration of viral genomes may have driven the evolution of disordered nucleic acid‐binding proteins. After RNA‐interference knockdown of the translational‐procession factor EEF2 to suppress translation in SY5Y‐APPSw cells, the RNA content of aggregates declined by >90%, while reducing protein content by only 30% and altering DNA content by ≤10%. This implies that cotranslational misfolding of nascent proteins may ensnare polysomes into aggregates, accounting for most of their RNA content. Abstract : Nucleic acid‐binding proteins are shown attaching to RNA and DNA, and then undergoing oxidation, thermal denaturation (reversible or irreversible), or other PTMs that destabilize their secondary structure sufficiently to allow aggregation to occur, an essentially irreversible process. Nascent polypeptides as they are synthesized by ribosomes provide another source of transiently misfolded proteins that can aggregate without oxidation or other trigger for denaturation. The sequence shown is not obligatory, in that disordered proteins could also bind nucleic acids after aggregating.